Hubungan Asupan Makan dan Aktifitas Fisik Terhadap Status Gizi Anak Usia Sekolah - Vianty Aldofin Tomasoa; Dary Dary; Dennys Christovel Dese (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Abstract Health problems in children, especially in terms of nutrition, are still a problem in Indonesia such as underweight and overweight, which are caused by physical activity, and vice versa, nutritional status affects children's physical activity. Nutritional status and physical activity play an important role in achieving good physical fitness, especially for school age children. Only 1 in 3 children who are active in physical activity every day. The purpose of this study was to determine the relationship between food intake, physical activity and nutritional status in school age children. This research uses a correlational quantitative approach. Respondents who were the subjects in this study were students in grades 3-6 at SDN 2 Saparua, totaling 120 students. The number of samples used in this study was determined using the Taro Yamane or Slovin formula which resulted in 93 students. The research instruments used in this study were a 2x24 hour food recall questionnaire, anthropometric examination, physical activity questionnaire of children (PAQ-C) for physical activity and nutritional status determined using BMI / U. The research data were processed using bivariate analysis with the help of statistical products and solutions (SPSS). Correlation analysis using Pearson. The results of hypothesis testing on food intake and physical activity with a statistical value of R = 0.652; R Square = 0.425. This means that the variables of food intake and physical activity simultaneously play a role in the nutritional status of the individual by 42.5%, while the remaining 57.5% is influenced by other factors that are not disclosed in this study. The better the score of physical activity and food intake, the better the nutritional status of the child.Keywords: food intake, physical activity, nutritional status